A vulnerabilidade jurídica do consumidor e a ação coletiva como instrumento de controle em face da estipulação abusiva da multa compensatória nos contratos de adesão - Mata, Poliana Moreira Delpupo (2018)
The aim of this study is to demonstrate the legal vulnerability of the consumer and collective action as an instrument of control in the face of the abusive stipulation of the compensatory fine in the adhesion contracts. For this, the present research starts from the analysis of the concept of consumer and supplier with the objective of distinguishing the relation of consumption of the other legal relations. Once the field of consumer relations has been delimited in the micro-system of Law 8.078/1990 – Code of Consumer Protection, we will discuss the principles of the Code, demonstrating the importance of the principles as limiting the abusive stipulation of the compensatory fine in the face of the consumer, giving emphasis on the principle of vulnerability, considering its legal vulnerability in the contractual relationship with the supplier of products and services. Next, we will study the consumption contracts and their historical evolution, differentiating the joint contracts from the contracts of adhesion, highlighting the use of this in the relations of consumption. With the increase of the adhesion contracts in the consumer relations, it is essential to study the unfair terms, since they are consumer protection rules in the face of the abuses committed by the suppliers in the contracts. In view of this, we will deal with the fine (penal clause), emphasizing the compensatory fine and the way in which the courts interpret the abusive stipulation of the compensatory fine in consumer contracts (reducing it to 10% based on article 413 of CC c/c Article 9 of Decree-Law 22.626/33), which we consider to be contrary to what is set forth in art. 51, which establishes nullity in the hypothesis of unfair terms, since the dialogue between the sources between the CDC and the CC (other infraconstitutional laws) will only occur when in the benefit of the consumer. Finally, we will demonstrate the importance of collective actions as an instrument to control the compensatory fines stipulated abusively in the consumer compliance contracts, in the face of consumer vulnerability